A critical review of the long-term disability outcomes following hip fracture. Issue 1 (December 2016) - Dyer, Suzanne; Crotty, Maria; Fairhall, Nicola; Magaziner, Jay; Beaupre, Lauren; Cameron, Ian; Sherrington, Catherine
Abstract Background Hip fractures are an increasingly common consequence of falls in older people that are associated with a high risk of death and reduced function. This review aims to quantify the impact of hip fracture on older people's abilities and quality of life over the long term. Methods Studies were identified through PubMed and Scopus searches and contact with experts. Cohort studies of hip fracture patients reporting outcomes 3 months post-fracture or longer were included for review. Outcomes of mobility, participation in domestic and community activities, health, accommodation or quality of life were categorised according to the World Health Organization's International Classification of Functioning and synthesised narratively. Risk of bias was assessed according to four items from the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement. Results Thirty-eight studies from 42 publications were included for review. Most followed a clearly defined sample from the time of fracture. Hip fracture survivors experienced significantly worse mobility, independence in function, health, quality of life and higher rates of institutionalisation than age matched controls. The bulk of recovery of walking ability and activities for daily living occurred within 6 months after fracture. Between 40 and 60 % of study participants recovered their pre-fracture level of mobility and ability to perform instrumental activities of daily living, while 40–70 % regained their level of independence for basic activities of daily living. For people independent in self-care pre-fracture, 20–60 % required assistance for various tasks 1 and 2 years after fracture. Fewer people living in residential care recovered their level of function than those living in the community. In Western nations, 10–20 % of hip fracture patients are institutionalised following fracture. Few studies reported impact on participation in domestic, community, social and civic life. Conclusions Hip fracture has a substantial impact on older peoples' medium- to longer-term abilities, function, quality of life and accommodation. These studies indicate the range of current outcomes rather than potential improvements with different interventional approaches. Future studies should measure impact on life participation and determine the proportion of people that regain their pre-fracture level of functioning to investigate strategies for improving these important outcomes.